2018
DOI: 10.1188/18.onf.308-326
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Cognitive Function and Associated Phenotypic and Genotypic Factors in Breast Cancer

Abstract: OBJECTIVES This study identified women with unique trajectories of executive function, concentration, and visual working memory before and during adjuvant therapy for breast cancer, and examined phenotypic and genotypic predictors associated with subgroups. SAMPLE & SETTING 399 postmenopausal women, of whom 288 were women with early-stage breast cancer and 111 were women without breast cancer, matched on age and years of education to the women with breast cancer, and all at an urban cancer center. METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 64 publications
(92 reference statements)
1
31
0
Order By: Relevance
“…Ten studies reported results on the influence of APOE genotypes on cognitive functioning in cancer patients. Six focused on breast cancer (BC) patients [19][20][21][22][23][24], one reported on both BC and lymphoma patients [25], and three reported on other patient groups [26][27][28]. The remaining seven studies reported results from studies investigating other genes than APOE, e.g., COMT [24,29] and BDNF [14,24], with five of these studies focusing on BC patients [14,[29][30][31][32], one on prostate cancer patients [33], and one on patients with mixed non-CNS cancers [34].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Ten studies reported results on the influence of APOE genotypes on cognitive functioning in cancer patients. Six focused on breast cancer (BC) patients [19][20][21][22][23][24], one reported on both BC and lymphoma patients [25], and three reported on other patient groups [26][27][28]. The remaining seven studies reported results from studies investigating other genes than APOE, e.g., COMT [24,29] and BDNF [14,24], with five of these studies focusing on BC patients [14,[29][30][31][32], one on prostate cancer patients [33], and one on patients with mixed non-CNS cancers [34].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Using the NIH Quality Assessment Tool [18], each study received a quality rating (range: 0-14). Eight studies [14,19,20,23,[25][26][27]33] were rated 'good quality' (>9 criteria met), and the remaining nine studies [21,22,24,[28][29][30][31][32]34] were rated 'fair quality' (5-9 criteria met). Study quality ratings are shown in Supplementary Table S3.…”
Section: Study Quality Assessment Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations